Psilocybin for major depressive disorder: a systematic review of randomized controlled studies - Li, Li-Juan; Mo, Yu; Shi, Zhan-Ming; Huang, Xing-Bing; Ning, Yu-Ping; Wu, Hua-Wang; Yang, Xin-Hu; Zheng, Wei (Frontiers in Psychiatry, 2024)
The purpose of this systematic review of randomized controlled trials (RCTs) was to evaluate the effectiveness, safety, and tolerability of psilocybin in adult patients with major depressive disorder (MDD). Methods: A systematic search (up to September 14, 2023) was conducted for RCTs that examined the efficacy, safety, and tolerability of psilocybin in physically healthy adult patients with MDD. Three independent researchers extracted data from publications where the primary outcome was a change in depressive symptoms, and key secondary outcomes were changes in anxiety symptoms and suicidal ideation, discontinuation rates for any reason, and adverse drug reactions (ADRs). Results: Five RCTs with 472 adult patients with MDD on psilocybin (n = 274) and controls (n = 198) were included. Two of the five RCTs (40%) reported mixed results, while the other three (60%) found that psilocybin had a beneficial effect on MDD treatment. Four RCTs (80%) assessing the anxiolytic effects of psilocybin for treating MDD found that psilocybin was significantly more effective than the control group in improving anxiety symptoms. Psilocybin was more effective than the control group in improving suicidal ideation in one out of five RCTs. Discontinuation rates were similar for any reason between the psilocybin group (2-13%) and the control group (4-21%) (P>0.05). Four RCTs (80%) reported ADRs in detail. The most common ADR in both groups was headache. Conclusion: Psilocybin was effective in improving depressive symptoms in over half of the included studies and reduced anxiety symptoms in patients with MDD. The long-term efficacy and safety of psilocybin for MDD treatment needs to be further investigated in large RCTs.